390-35=355
355-10w
355/10=35.5
355-10(35.5)
35 and a 1/2 weeks
36 weeks to have the full amount needed
Answer:
36th weeks
Step-by-step explanation:
Kelsey has saved $35 to buy a video game worth $390.
She plans to save additional $10 per week.
Let w represents number of week.
Let s represents total saving in w weeks.
Addition saving per week = $10
In w weeks saving = 10w
Previous saving amount = $35
Total saving in w week, s = 35 + 10w
Expression which represents total saving in w weeks
s = 35 + 10w
Now find number of weeks to save $390
So, put s=390 and solve for w
35 + 10w = 390
10w = 390 - 35
w = 355÷10
w = 35.5
Hence, Kelsey will save $390 in 36th weeks.
Can some one help me plz??
paralell to y=4x-6 through (12,10)
ANSWER
The line that is parallel to [tex]y=4x-6[/tex] through [tex](12,10)[/tex] is [tex]y=2x-14[/tex].
EXPLANATION
The equation that is parallel to the line [tex]y=4x-6[/tex] has a slope that is equal to the slope of this line.
By comparing this equation to the general slope intercept form,
[tex]y=mx+c[/tex],this line has slope [tex]m=2[/tex].
Hence the line parallel to this line also has slope [tex]m=2[/tex].
Let [tex]y=mx+b[/tex] be the equation of the line parallel to the line
[tex]y=4x-6[/tex]
We can substitute [tex]m=2[/tex] to obtain;
[tex]y=2x+b[/tex]
If the line passes through the point [tex](12,10)[/tex],then this point must satisfy its equation.
We substitute [tex]x=12[/tex] and [tex]y=10[/tex] to obtain;
[tex]10=2(12)+b[/tex]
We this equation for [tex]b[/tex].
[tex]\Rightarrow 10=24+b[/tex]
[tex]\Rightarrow 10-24=b[/tex]
[tex]\Rightarrow -14=b[/tex]
We substitute this value of [tex]b=-14[/tex] in to [tex]y=2x+b[/tex] to get;
[tex]y=2x+-14[/tex].
Hence the equation of the line that is parallel to [tex]y=4x-6[/tex] through [tex](12,10)[/tex] is [tex]y=2x-14[/tex].
challenge questions 1
9)
[tex]\frac{24z^{5}y^{4}}{3z^{-2}y^{5}} = \frac{24}{3}*\frac{z^{5}}{z^{-2}}*\frac{y^{4}}{y^{5}} = \frac{8}{1} *\frac{z^{5+2}}{1}*\frac{1}{y^{5-4}} = \frac{8z^{7} }{y}[/tex]
11)
(a²b)³ = a²⁽³⁾b¹⁽³⁾ = a⁶b³
12)
The exponent tells you how many places to move the decimal. The positive/negative sign tells you which direction to move the decimal (negative is left, positive is right).
8.4 x 10⁻⁵ move the decimal 5 places to the left = 0.000084
Find the original price of a pair of shoes if the sale price is $45 after a 25% discount
$60
$45 is 75% of the original price. 75/3 is 25, so divide 45/3=15. $15 is 1/4 of the original price. 15*4=60
The original price of the pair of shoes is $60.
To find the original price of a pair of shoes, we can use the given information that the sale price is $45 after a 25% discount.
Let's assume the original price of the shoes is "x" dollars.
The discount of 25% means that the sale price is equal to 75% (100% - 25%) of the original price.
Mathematically, we can express this as:
Sale price = Original price * (Discount percentage in decimal form)
$45 = x * (0.75)
To find the original price (x), we divide both sides of the equation by 0.75:
$45 / 0.75 = x
x = $60
Therefore, the original price of the pair of shoes is $60.
To know more about original price:
https://brainly.com/question/731526
#SPJ2
Please help. I will reward brainly
Positive, 72 minus negative 9 is the same thing as 72+9, which equals 81. So the answer is positive
Find f if f(x)=23; 23= x²+7
Hanna walks 1 2/3 miles to school. After school she walks 1 1/2 mikes to work. How many miles does she walk before and after school?
Hanna walks a total of 3 1/6 miles before and after school.
To find how many miles Hanna walks before and after school, we can add the distances she walks to school and to work.
Distance to school = 1 2/3 miles
Distance to work = 1 1/2 miles
To find the total distance Hanna walks before and after school, add the two distances:
Total distance = 1 2/3 + 1 1/2
To add these fractions, we need to convert them to have a common denominator, which is 6:
1 2/3 = (3/3 + 2/3) = 5/3
1 1/2 = (3/2)
Now, we can add the fractions:
Total distance = 5/3 + 3/2
To add these fractions, we need to have a common denominator, which is 6:
Total distance = (5/3) * (2/2) + (3/2) * (3/3)
Total distance = 10/6 + 9/6
Now, add the fractions:
Total distance = 19/6
We can simplify this fraction:
Total distance = 3 1/6 miles
So, Hanna walks a total of 3 1/6 miles before and after school.
To know more about miles click here :
https://brainly.com/question/14997853
#SPJ2
Domain of the function of a graph with coordinates (-3,-2)
Answer:
Domain is -3
Step-by-step explanation:
Given that coordinate of a graph is (-3, -2)
We have to find out the domain.
We know that if A and B are two sets, a mapping from A to B is the subset of cartesian product AxB.
Domain is the set of values of A which have images in B.
Use the above definition.
We have A = {-3,...} and B = {-2,....}
The mapping is from -3 to -2
Hence domain is -3
John and his family went out to eat at the bill of the food was $65 and it has a 20% tip what was the total cost other meal including the tip
$78
$65x.20=13
65+13=$78
Write the numerical expression for the product of 8 and the sum of 9 and 11.3. Then evaluate it.
Solution: The numerical expression is [tex]8\times (9+11.3)[/tex] and the value of this expression is 162.4.
Explanation:
The sum of 9 and 11.3 is written as [tex](9+11.3)[/tex].
The product of 8 means the expression should multiply by 8.
According to the given information the the product of 8 and the sum of 9 and 11.3 is written as [tex]8\times (9+11.3)[/tex].
To evaluate the value of the expression first we have to add 9 and 11.3 after that multiply the result by 8.
[tex]8\times (9+11.3)=8\times (20.3)\\8\times (9+11.3)=162.4[/tex]
Therefore, the numerical expression is [tex]8\times (9+11.3)[/tex] and the value of this expression is 162.4.
Answer:
162.4
Step-by-step explanation:
To write the numerical expression for the product of 8 and the sum of 9 and 11.3 we need to follow these steps:
Sum of 9 and 11.3 is given as follows:
[tex](9+11.3)[/tex]
Now the product of 8 and the sum of 9 and 11.3 is:
[tex]8(9+11.3)[/tex]
So the required expression is:
[tex]8(9+11.3)[/tex]
Solving the above expression we get:
[tex]8(9+11.3)=8(20.3)=8 \times 20.3=162.4[/tex]
I need help solving this question
C.
Combine like terms when adding f(x) and g(x) 2x^2 + x^2 and 1 + (-7) = 3x^2 - 6
The cost of driving a car includes both fixed costs and mileage cost. Assume that a costs $176.10 per month for insurance and car payments and $0.25 per mile for gasoline, oil, and routine maintenance.
$176.10 per month for insurance and car payments and $0.25 per mile for gasoline, oil, and routine maintenance.
(a) find values for m and b so that y=mx+b Modells the monthly cost of driving the car X miles
(B) what does the value of b represents ?
Y=.25x+176.10 Y is the monthly cost and B would be the cost of the insurance every month. X is the amount of miles driven since the .25 stays constant but the amount of miles you drive in a month is different every month, Hence, needs to be a variable that can be adjusted,
A - The value of b, $176.10, represents the fixed costs like insurance and car payments, which remain constant regardless of the number of miles driven. B - It serves as the baseline monthly cost for driving the car.
(a) To model the monthly cost of driving the car (y) in terms of the number of miles driven (x), you can use the equation y = mx + b, where:
y represents the monthly cost of driving the car.
x represents the number of miles driven.
m represents the cost per mile for gasoline, oil, and routine maintenance, which is $0.25 in this case.
b represents the fixed costs, including insurance and car payments, which are $176.10 per month.
So, the values for m and b in this scenario are:
m = 0.25 (the cost per mile)
b = 176.10 (the fixed monthly costs)
Therefore, the equation to model the monthly cost of driving the car is:
y = 0.25x + 176.10
(b) The value of b, which is 176.10 in this equation, represents the fixed costs associated with driving the car. In this case, it includes the monthly insurance and car payment expenses. These are costs that do not depend on how many miles you drive.
Instead, they remain constant every month. So, b represents the baseline or starting point for the monthly cost of driving the car. Even if you were to drive zero miles in a month, you would still have to pay these fixed costs.
To learn more about fixed costs
https://brainly.com/question/20670674
#SPJ2
−(7y+0.6)=3.6−y
PLEASE ANSWER QUICKLY
Answer:
y=-0.7
Step-by-step explanation:
−(7y+0.6)=3.6−y
-7y+-0.6=3.6−y
-6y+-0.6=3.6
-6y=4.2
y=-0.7
Solve this linear system by graphing
x-y=6
2x=12+2y
To solve the linear system by graphing, convert the equations to slope-intercept form, plot the lines, and find the point of intersection.
Explanation:To solve the given linear system by graphing, we need to graph both equations on the same coordinate plane and find the point of intersection.
Step 1: Convert both equations into slope-intercept form, y = mx + b.
Step 2: Plot the y-intercepts (b values) of both equations and use the slopes (m values) to draw the lines.
Step 3: The point where the lines intersect is the solution to the system of equations. In this case, the solution is x = 6 and y = 0.
Determine the measure of the unknown labeled angles in the diagram above
value of 3x^2 +4y^2 if x=2, y=1, and z= -3
[tex]3x^2+4y^2\\\\\text{Put the values of x=2, y=1 and z=-3 to the expression:}\\\\3(2^2)+4(1^2)=3(4)+4(1)=12+4=16[/tex]
Substituting the provided values of x and y into the equation 3x^2 +4y^2 gives a final result of 16.
Explanation:The question is asking for the value of the mathematical expression 3x^2 +4y^2 when x is 2 and y is 1. To find this, we substitute the values of x and y into the expression.
Substitute x = 2 into the equation: 3*(2)^2 = 3*4 = 12 Substitute y = 1 into the equation: 4*(1)^2 = 4*1 = 4 Add the results: 12 + 4 = 16
Therefore, the value of 3x^2 +4y^2 when x=2 and y=1 is 16.
Learn more about Substitution into expression here:https://brainly.com/question/37676786
#SPJ3
How do I solve for y?
First we know that,
3x+15=5x-65 because of vertical angle thr.
y=y because of reflex property
there are 360 degrees in a circle so..
3x+15+5x-65+2y=360
3x+15=5x-65
x=40
so each 2 of the angles are...(40*3+15)=135
Then your new equation is
135+135+2y=360
2y=90
y=45
Hope this helps :)
212x−34(2x+5)=38
which one
a) x=−458
b) x=−338
c) x=418
d) x=538
Answer:
c
Step-by-step explanation:
What does a represent?
A.foci
B. Minor axis
C. Major axis
S. Vertices.
Math written response questions, please help :( thank you
Use Pythagorean Theorem (a² + b² = c²) to find the lengths of the sides. You can also use the distance formula.
6² + 14² = d²
36 + 196 = d²
232 = d²
15.23 ≅ d
2² + 5² = d²
4 + 25 = d²
29 = d²
5.39 ≅ d
Next, use the Perimeter formula:
P = 2L + 2w
= 2(15.23) + 2(5.39)
= 30.46 + 10.78
= 41.24
For #6, Use the Area formula:
A = L x w
= 5.39 x 41.24
= 222.28
The dimensions of a rectangle can be given by x+7 and x+2. If the area of the rectangle is 66 square inches, what are the dimensions of the rectangle?
to solve for the dimensions (x+7)(x+2)=66,
we can first use the foiling method to simplify the left side.
x^2 + 2x + 7x + 14 = 66
x^2 + 9x + 14 = 66
now, subtract 66 from both sides.
x^2 + 9x - 52 = 0
now, split this into two parentheses.
(x + 13)(x - 4)
since the root of -13 would give you negative values, x=4. This means that the dimensions of the rectangle are 11 and 6.
The dimensions of the rectangle is 11 by 6 inches
How to determine the dimensions?The dimensions are given as:
x + 7 and x + 2
The area is given as:
Area = 66
The area of a rectangle is:
Area = Length * Width
So, we have:
(x + 7) * (x + 2) = 66
Express 66 as 11 * 6
(x + 7) * (x + 2) = 11 * 6
By comparison, we have:
x + 7 = 11 and x + 2 = 6
Solve for x
x = 4 and x = 4
Substitute 4 for x in x + 7 and x + 2
x + 7 = 4 + 7 = 11
x + 2 = 4 + 2 = 6
Hence, the dimensions of the rectangle is 11 by 6 inches
Read more about areas at:
https://brainly.com/question/24487155
A prism's volume is given by the expression
6k2 – 13k + 5. The area of the base of the
prism is 2k – 1.
Which expression represents the height of the prism?
k + 4
3k – 5
3k – 8 +
4k – 7 –
The volume of any prisma no matter wich one side it have got the following formula:
V=Ab*h where Ab is the base area and h is called height.
From our data we know the volume (6k^2-13K+5) and we know the base area (2k-1). Inserting this data in the general formula we got:
6k^2-13K+5=(2k-1)*h, solving for our unknown variable the height h
h=6k^2-13K+5/2k-1
factoring numerator :
h=(3k-5)(2k-1)/2k-1 simplifying
h=3k-5
The answer is 3k-5
Remark
The Volume = B * h
V = 6k^2 - 13k + 5
B = 2k - 1
h = ??
The volume will factor into (2k - 1)(3k - 5)
You can tell that one of the factors is 2k - 1 because that is the given amount for the base. You need only find the other factor. 3k is needed to multiply 2k to 6k^2.
- 1 needs - 5 to get the answer to 5
So the other factor is 3k - 5
Solution
V/b = h
(6k^2 - 13k + 5)/(2k - 1)
(3k - 5)(2k - 1) / (2k - 1) The (2k - 1)s Cancel out
Answer
B = 3k - 5 Second one down.
Lamar is solving the equation x2−12x=−6 by completing the square. Which shows Lamar's next step and the solution to the equation?
To solve the equation x²−12x=−6, Lamar should first move the constant to the other side and complete the square, leading to x = 6 ±√30. This equation, which is a type of quadratic or second-order polynomial, may have two solutions, a typical characteristic of such equations.
Explanation:The equation presented is x²−12x=−6. To solve this equation by completing the square, we first move the constant term to the other side, which leads to x² - 12x = -6, or x² - 12x + 36 = -6 + 36. We added 36 on both sides because (12/2)² = 36, which is a step in completing the square for the equation. Thus, we have (x-6)² = 30. Now, solve for x: x - 6 = ±√30, so x = 6 ±√30.
This method, known as completing the square, is a typical approach to solving quadratic equations. The general quadratic equation ax²+bx+c = 0 can also be solved using the quadratic formula -b ± √(b² - 4ac) / 2a. With both methods, remember that a quadratic equation will usually have two solutions, as it is a second-order polynomial.
Learn more about Completing the Square here:https://brainly.com/question/4822356
#SPJ12
Combine like terms to simplify the expression. 5x + 4 + 2x + 5
7x+9
5x+2x= 7x
5+4=9
7x + 9 is the result when combining like terms.
Answer:
7x+9
Step-by-step explanation:
Add the numbers
5x + 4 + 2x + 5
5x+9+2x
Combine like terms
5x+9+2x
7x+9
Solution:
7x+9
3y^2/9y^4 state restrictions and simplify
Step 1. Take out the constants
3/9 y^2y^4
Step 2. Simplify 3/9 to 1/3
1/3 y^2y^4
Step 3. Simplify
y^2y^4/3
Step 4. Use the Product Rule
y^2 + 4/3
Step 5. Simplify 2 + 4 to 6
y^6/3
q-r=r, for r formula for the variable
I really need some help so please help me!!!
I'll mark brainliest for the best answer please!!!
here is the options
2.50
20
the daily profit of the taxi cab driver
the initial fee before any miles are traveled
3
the cost per mile traveled
a pet boarder keeps a dog to go cat ratio of 5:2 . if the boarder has room for 98 animals then how many of them can be dogs
For every 7 animals, you have 5 dogs to 2 cats. So divide 98 by 7 and you get 14 groups of 7.
Multiple 14 times 5 dogs and you get 70
Multiple 14 times 2 cats and you get 28
70 + 28 = 98.
Which expression is equivalent to 3/4 - 1/2?
stacey buys 6 pounds of chicken for $39. How much will she pay for 11 more pounds of chicken.
So she pays 6 lb of chicken for $39 then $39/6 = $6.30 is the price per pound.
11lb + 6lb = 17lb total of chicken then multiply it by the price per pound
17($6.50) = $110.50
Final answer:
Stacey will pay $71.50 for 11 more pounds of chicken.
Explanation:
To figure out how much Stacey will pay for 11 more pounds of chicken, we can use the given information that she bought 6 pounds of chicken for $39.
First, we need to find the cost of chicken per pound. To do this, we divide the total cost of chicken ($39) by the number of pounds (6). So, $39 / 6 = $6.50 per pound.Next, we can calculate the cost of 11 more pounds of chicken by multiplying the cost per pound ($6.50) by the number of pounds (11). So, $6.50 * 11 = $71.50.Therefore, Stacey will pay $71.50 for 11 more pounds of chicken.